Phonological Sketch of Malay Jambi Language of Sarolangun, Indonesia - Nadra Nadra; Muhammad Yusdi; Å»aneta Krulikowska (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
This research is a cross-sectional sample survey with a qualitative approach of Malay Jambi's phonology in Sarolangun Regency. The data was collected in the field using observation and interview methods. It has a form of notes, interview transcriptions, and audio and video recordings. The data was analyzed using a phonetic articulator matching method with a diving-key-factors technique as a basis. The results are presented based on the phonetic symbols of the IPA Chart (revised 2005). As found in the research, Malay Jambi of Sarolangun has six vowels and twenty consonants, one of which does not occur in native Malay Jambi words. Beyond the phonological system description, this paper discusses various features found in Sarolangun like nasalization and laxing of vowels, consonant and syllable deletion, or glide insertion.